Strengthening clinical microbiology laboratories and prevention programs: a call to action for better infection control - Abayeneh Girma (Universa Medicina, 2026)
The coronavirus disease 2019 (COVID-19) pandemic has revealed severe vulnerabilities in the global clinical laboratory systems, especially in low- and middle-income countries, where diagnostic capacity is still poor. As the world emerges from the acute phase of the pandemic, antimicrobial resistance (AMR) has re-emerged as the silent pandemic demanding urgent attention. Clinical microbiology laboratories are not just support services, they are the first line of defense against the disease outbreaks, healthcare-associated infections, and the increased risk of the drug-resistant pathogens. However, in most environments these laboratories are poorly funded, staffed and equipped. Enhancement of clinical microbiology laboratories should, therefore, be considered as one of the health priorities in the world.